Innovation in Government: Strategies for Effective Public Service Delivery (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to identify and analyze the factors that drive and hinder innovation in the public sector. The goal is to understand how these factors influence the quality of public service delivery and provide practical recommendations for policymakers and practitioners in the public sector. The study focuses on the public sector in North Sumatra Province, Indonesia, to offer context-specific insights. The research adopts a quantitative approach using survey methods. The sample consists of 300 public sector employees from various departments within the North Sumatra Provincial Government, selected through purposive sampling. Data collection involved questionnaires designed to measure factors driving and hindering innovation, as well as interviews with key personnel to gain deeper insights. The data were analyzed using descriptive statistics, regression analysis, and thematic analysis. This study underscores the critical role of management support, technological access, and a supportive organizational culture in promoting innovation in the public sector. It also highlights significant barriers such as resistance to change, resource constraints, and rigid bureaucracy. Addressing these barriers through comprehensive and strategic approaches, including bureaucratic reform and effective communication, can create an environment conducive to innovation. This, in turn, can enhance the quality of public services and meet the increasingly complex needs of society. The findings provide valuable insights for policymakers and public sector managers aiming to foster sustainable innovation and improve public service delivery.